SGOTL: A Computer Program for Modeling High-Resolution, Height-Dependent Gravity Effect of Ocean Tide Loading - Cheinway Hwang Jiu-Fu Huang (Terrestrial, Atmospheric and Oceanic Sciences, 2012)

(untitled)
SGOTL, a computer package coded in FORTRAN, has been developed to model the gravity effect due to ocean tide loading (OTL), especially for a coastal station with large ocean tides. SGOTL uses a regional and a global tide model to account separately for near (inner) and far (outer) zone contributions, and optimizes an inner-zone region and grid interval for numerical convolution. Height dependent Green¡¦s functions for Newtonian and elastic effects are developed. The coastline is defined by the full-resolution GMT shoreline, and optionally a digital elevation model (DEM). A case study using gravity observations at the Hsinchu superconducting gravity station and some offshore islands around the Taiwan Strait suggests that SGOTL outperforms some selected global OTL programs and achieves an accuracy of 0.1 μGal for 8 leading tidal constituents.